CORRELATION ANALYSIS BETWEEN THE MORPHOMETRIC CHARACTERISTICS OF THE HEAD OF NUCLEUS CAUDATUS AND THE INTENSITY OF PSYCHOTIC MANIFESTATION IN SCHIZOPHRENIA - Stojanovic Zlatan; Stojanovic Vukadinovic Sanja; Macanovic Gordana (Sanamed, 2018)
Introduction: One of the significant functional disorders of the central nervous system in patients with schizophrenia is the increased activity of the mesolimbic dopaminergic system. By the nigrostriatal pathway, the caudate nucleus is closely related to other dopaminergic systems of the brain. Since the function of caudate nucleus relies on the action of dopamine in the brain; the role of this anatomical structure in the pathogenesis of schizophrenia is not sufficiently clarified. The aim of this paper was to examine whether the caudate nucleus participates in the modulation of the intensity of psychotic manifestations in schizophrenia. Patients and Methods: The study included a total of thirty-one patients with schizophrenia. Diagnosis of the schizophrenia was based on the DSM-IVcriterion (Diagnostic and Statistical Manual of Mental Disorders, fourth edition), and the intensity of psychotic manifestations was evaluated by using Brief Psychiatric Rating Scale (BPRS). The size of the caudate nucleus was determined on axial non-contrast CT images on the surface of the largest cross-section using AutoCAD 2007 digital morphometry. The statistical data were processed by the SPSS 16.0 program package. The statistical conclusions are presented on the basis of two-tail p <0.05. Results:In this study, we have observed a negative correlation between the area as well as the perimeter of the left caudate nucleus head section and the intensity of the psychotic manifestations (area: regression coefficient B = -0.17, p = 0.050, perimeter: regression coefficient B = -0.010, p = 0.012). On the right hemisphere of the brain we observed only a negative correlation of the intensity of the psychotic manifestations from the perimeter of the head section of caudate nucleus (regression coefficient B = -0.013, p = 0.011). Conclusion: In our research we found that the higher intensity of psychotic manifestations in schizophrenia was accompanied with the smaller area and the perimeter of left caudate head as well as the smaller perimeter of the head of right caudate nucleus. The finding of the dependence of the intensity of psychotic manifestations on the perimeter of the right caudate head and not on its area speaks in favor of the caudate head surface deformations as one of the markers of intensity of psychotic manifestations in patients with schizophrenia.